ANALYSIS OF VEHICLE OPERATING COSTS USING METHOD (PACIFIC CONSULTANT INTERNATIONAL) PCI ON SEMARANG TOLL ROAD SECTION A AND NON-TOLL ROAD (KRAPYAK-JATINGALEH) - Mahendra, Rega; Asih, Veni; Suwandi, Putri Anggi Permata; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2022)
Abstract. The Semarang toll road is the only toll road network in the city of Semarang at this time. The construction of toll roads aims to reduce congestion and improve travel time efficiency. In addition, the benefit of toll roads is that toll road users will benefit in the form of vehicle operational cost savings (BOK) and time compared to if they pass through non-toll roads. For alternative routes or non-toll roads, conventional roads can be chosen by motorists without passing through toll roads. This study aims to calculate vehicle operating costs (BOK), vehicle operating cost benefits (BKBOK) using the Pacific Consultant International (PCI) method as a limit to determine toll rates and analyze the comparison of Vehicle Operating Costs (BOK) on toll and non-toll roads. . Data collection techniques in this study used primary and secondary data collection techniques. The analysis was carried out using an interactive analysis model. The calculation of vehicle operating costs using the PCI method is taken from the lowest vehicle operating costs from various speed variations. For toll roads, the lowest vehicle operating costs occur at a speed of 60 km/hour with a total BOK of Rp. 6,803.54. Meanwhile, for non-toll roads, the lowest vehicle operating costs occur at a speed of 60 km/hour with a total BOK of Rp. 10,641.27. According to the analysis we have obtained, toll roads are cheaper than non-toll roads. For road users in the city of Semarang, it is recommended to use the Semarang section A toll road compared to non-toll roads, because vehicle operating costs are more efficient and have a much faster travel time.Keyword : BOK,BKBOK, speed, PCI, Toll Road